“I can be pro-abortion and pro-birth”: Opportunities and challenges for full spectrum care among doulas in Georgia - Lindsey, Alyssa; Narasimhan, Subasri; Sayyad, Ayeesha; Turner, Daria; Mosley, Elizabeth A. (Frontiers in Global Women's Health, 2023)
Background The work of full spectrum doulas (i.e., non-medically trained care workers offering support before, during, and after pregnancy including abortion)—is increasingly important as abortion access decreases across the U.S. Few studies have examined the work of community-based doulas in restrictive abortion settings or how they might further incorporate full spectrum care. As part of the community-engaged mixed methods Georgia Doula Study, this analysis examines the scope of work of community-based doulas regarding full spectrum and abortion services, doula opinions on full spectrum and abortion work, and potential barriers and facilitators for full spectrum doula care in metro-Atlanta, Georgia. Methods From October 2020 to February 2022, the team recruited 20 community-based doulas with 8 who provide full spectrum services including abortion. Surveys covered demographics, doula scope of work, family planning attitudes, and abortion stigma. Survey data were analyzed using descriptive and bivariate statistics. In-depth interviews further explored those topics. They were de-identified and thematically analyzed using a semi-deductive approach. Results The findings are organized around five themes: (1) doulas of all kinds center reproductive autonomy; (2) abortion doulas play important roles in reproductive autonomy; (3) doulas have mixed feelings about contraceptive counseling; (4) abortion doulas provide diverse services carrying numerous benefits in a stigmatized environment; and (5) abortion doulas experience challenges including stigma but they offer solutions. All but two doulas in this study were interested in learning how to incorporate contraception and abortion services in their current scope of work, and most participants supported the role of full spectrum doulas. Conclusion This analysis highlights the experiences of abortion and full spectrum doulas, reactions of the larger doula community to those services, and facilitators and barriers to full spectrum doula care in a restrictive abortion setting. There are urgent needs and opportunities for full spectrum doulas to offer life-protecting services to pregnant people across the U.S. and globally. Coordination efforts for U.S. abortion care post-Roe v. Wade must include community-based doulas, who are largely open to aiding abortion clients through education, connection to care, and emotional support.